2019
DOI: 10.1111/ejh.13271
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of follicular lymphoma: A comprehensive review

Abstract: Follicular Lymphoma (FL) is an indolent lymphoma and may have various clinical courses. Worldwide, FL is the second most common non-Hodgkin lymphoma (NHL) type after diffuse large B-cell lymphoma. In this review article, the author is discussing relevant diagnostic tools, prognostic factors, and updated study results on the management of patients with newly diagnosed and relapsed/refractory FL.Controversies in the treatment, maintenance therapy, stem cell transplantation, and novel treatment approaches will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 79 publications
0
31
0
2
Order By: Relevance
“…There is no standard therapy and the relapsing nature further necessitates serial treatment 33,34) . Novel approaches for relapsed or refractory FL have been studied such as: rituximab plus lenalidomide (ORR 64%, CR 20%); bruton tyrosine kinase (BTK) inhibitor ibrutinib (ORR 38%, CR 13%); bendamustine (ORR 63%, CR 12%); and obinutuzumab plus bendamustine followed by obinutuzumab maintenance (ORR 69%, CR 11%), whether as a single-agent or in combination 33) . Our study showed an ORR of 56.9% (CR rate of 15.8%) with copanlisib monotherapy in the indolent NHL cohort, which consisted mostly of FL (70%).…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard therapy and the relapsing nature further necessitates serial treatment 33,34) . Novel approaches for relapsed or refractory FL have been studied such as: rituximab plus lenalidomide (ORR 64%, CR 20%); bruton tyrosine kinase (BTK) inhibitor ibrutinib (ORR 38%, CR 13%); bendamustine (ORR 63%, CR 12%); and obinutuzumab plus bendamustine followed by obinutuzumab maintenance (ORR 69%, CR 11%), whether as a single-agent or in combination 33) . Our study showed an ORR of 56.9% (CR rate of 15.8%) with copanlisib monotherapy in the indolent NHL cohort, which consisted mostly of FL (70%).…”
Section: Discussionmentioning
confidence: 99%
“…We then determined whether the ULA-MALC model was adapted for a larger scale drug testing assay. Thus, we tested five different drugs known to directly target different pathways in FL [2,41] and determined their efficacy based on: i) their impact on morphology (area and roundness) measurable on entire ULA-MALC and ii) cell death induction quantified in a dissociated or whole 3D model. Each molecule was also tested in the presence of RTX or GA101 as used in the clinic [2,42].…”
Section: Drug Sensitivity Testingmentioning
confidence: 99%
“…FL usually has an indolent course and excellent overall survival. However, the disease remains incurable with conventional approaches and is characterized by repeated relapses [1,2]. Thus, FL research should focus on the development of new and more efficient molecules targeting key pathways leading to disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Adding rituximab or chemotherapy to radiation lacks an overall survival benefit, and thus it is not recommended. [ 59 ] In affected body regions with nonbulky disease where radiation is expected to cause significant morbidity (i.e., abdomen), observation is a reasonable option. Patients with bulky disease may be treated with chemotherapy regimens, as in advanced stages of disease.…”
Section: Indolent Lymphomamentioning
confidence: 99%